2018
DOI: 10.1002/ps.4896
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of glyphosate resistance and response to alternative herbicide‐based management in populations of the three Conyza species introduced in southern Spain

Abstract: The results indicate that non-target site resistant (NTSR) mechanisms explain resistance in C. bonariensis and C. canadensis, whereas both NTSR and target site resistant (TSR) mechanisms contribute to resistance in C. sumatrensis. The results obtained in the field trials suggest that the resistance problem can be solved through integrated weed management. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 47 publications
12
50
0
Order By: Relevance
“…In our case, there were no significant differences in terms of the EPSPS basal activity between the resistant and susceptible populations, with values ranging from 0.10 to 0.11 µmol phosphate µg total soluble protein (TSP) −1 (Figure 1). No additional data about Sorghum halepense EPSPS activity is available for comparison, but our values were similar to those observed in other glyphosate-susceptible EPSPS enzymes, such as those isolated from several Conyza species [26]. Therefore, even in a polyploidy species such as Johnsongrass, with multiple genes encoding the EPSPS protein, the overexpression of the EPSPS gene leading to multiple functional copies of the EPSPS protein does not seem to be the mechanism of resistance, as EPSPS basal activity remains the same no matter the biotype tested.…”
Section: Epsps Basal Activity and Inhibitionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our case, there were no significant differences in terms of the EPSPS basal activity between the resistant and susceptible populations, with values ranging from 0.10 to 0.11 µmol phosphate µg total soluble protein (TSP) −1 (Figure 1). No additional data about Sorghum halepense EPSPS activity is available for comparison, but our values were similar to those observed in other glyphosate-susceptible EPSPS enzymes, such as those isolated from several Conyza species [26]. Therefore, even in a polyploidy species such as Johnsongrass, with multiple genes encoding the EPSPS protein, the overexpression of the EPSPS gene leading to multiple functional copies of the EPSPS protein does not seem to be the mechanism of resistance, as EPSPS basal activity remains the same no matter the biotype tested.…”
Section: Epsps Basal Activity and Inhibitionsupporting
confidence: 84%
“…Therefore, even in a polyploidy species such as Johnsongrass, with multiple genes encoding the EPSPS protein, the overexpression of the EPSPS gene leading to multiple functional copies of the EPSPS protein does not seem to be the mechanism of resistance, as EPSPS basal activity remains the same no matter the biotype tested. In addition, there were no significant differences in the 50% inhibition of EPSPS activity (I 50 ) values among all the populations tested, with estimated values ranging from 2.6 (GR6) to 3.4 (GR1) µM (Figure 1), which were even lower than those observed in other weed populations with glyphosate-susceptible EPSPS enzymes [26,27]. Therefore, a change of the sensitivity to glyphosate of the EPSPS enzyme is not the mechanism of resistance in the resistant populations.…”
Section: Epsps Basal Activity and Inhibitionmentioning
confidence: 78%
See 1 more Smart Citation
“…Several studies have been conducted in Conyza spp. with the objectives to understand the GR mechanisms (Feng et al, 2004;Ferreira et al, 2008;Peng et al, 2010;Ge et al, 2014;Cardinali et al, 2015;Tani et al, 2015;Moretti et al, 2017;Kleinman and Rubin, 2017;González-Torralva et al, 2017;Hereward et al, 2018;Amaro-Blanco et al, 2018). These studies have found that the GR mechanisms are related to herbicide transport, translocation, uptake, metabolism, and alterations at the 5-enolpyruvylshikimate 3-phosphate synthase (EPSPS) enzyme, which is the glyphosate target site.…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate inhibits the enzyme 5-enolpyruvlshikimate-3-phosphate synthase (EPSPS), which catalyzes the reaction of shikimate-3-phosphate and phosphoenolpyruvate to form 5-enolpyruvil-shikimate-3-phosphate (Fernandez et al, 2015;Gonz alez-Torralva et al, 2012). Inhibition of EPSPS prevents the biosynthesis of phenylalanine, tryptophan, tyrosine, and other aromatic compounds in sensitive plants (Amaro-Blanco et al, 2018;Tahmasebi et al, 2018). In Turkey, glyphosate is the most widely used herbicide and is registered on more than 70 crops, including peach (Torun, 2017).…”
mentioning
confidence: 99%